Cinta Beda Agama dalam Bingkai Moderasi Beragama: Antara Realitas Sosial dan Nilai Keberagaman (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This research examines the issue of interfaith marriage in the context of religious moderation in Indonesia. This research uses a qualitative method with a library research approach. Based on Dukcapil data from 2022, 34.6 million couples were recorded as "unregistered marriages" due to interfaith marriages. showing strong tension due to the presence of regulations and religious doctrines that tend to be exclusive. By comparing the perspectives of Islam, Catholicism, and Hinduism, it was found that there are differences in doctrinal limitations regarding interfaith marriage practices. This shows how complex the relationship is between social structures and religious teachings in marriage. Moreover, this research found that there is a contradiction between the dominant interpretation of marriage law based on religious beliefs and the constitutional right to form a family (Article 28B paragraph 1 of the 1945 Constitution). As a solution, the paradigm of religious moderation is offered. This paradigm emphasizes justice, love, and tolerance as the fundamental principles of inclusive marriage. This study suggests changes to the legal and theological framework to adapt to a multicultural society.